Genome-Scale Approaches to Identify Genes Essential for Haemophilus influenzae Pathogenesis - Wong, Sandy M.; Akerley, Brian J. (Frontiers in Cellular and Infection Microbiology, 2012)
Haemophilus influenzae is a Gram-negative bacterium that has no identified natural niche outside of the human host. It primarily colonizes the nasopharyngeal mucosa in an asymptomatic mode, but has the ability to disseminate to other anatomical sites to cause otitis media, upper and lower respiratory tract infections, septicemia, and meningitis. To persist in diverse environments the bacterium must exploit and utilize the nutrients and other resources available in these sites for optimal growth/survival. Recent evidence suggests that regulatory factors that direct such adaptations also control virulence determinants required to resist and evade immune clearance mechanisms. In this review, we describe the recent application of whole-genome approaches that together provide insight into distinct survival mechanisms of H. influenzae in the context of different sites of pathogenesis.